(untitled) (Communications in Computational Physics, 2018)
In this paper, we simulate the pressure driven fluid flow at the pore scale level through 2-D porous media, which is composed of different curved channels via the lattice Boltzmann method. With this direct simulation, the relation between the tortuosity and the permeability is examined. The numerical results are in good agreement with the existing theory.